CLIL (CONTENT AND LANGUAGE INTEGRATED LEARNING) IN UZBEKISTAN - Jumaboyeva Sevinchoy Davronbek qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article analyzes the use of CLIL (Content and Language Integrated Learning) in Uzbekistan, its effectiveness, current challenges, and future prospects. It highlights how CLIL helps students acquire both foreign language skills and subject-specific knowledge simultaneously.